Combining sub-surface fertigation with conservation agriculture in intensively irrigated rice under rice-wheat system can be an option for sustainably improving water and nitrogen use-efficiency - Rana, B.; Parihar, Chiter Mal; Jat, M. L.; Patra, K.; Nayak, H. S.; Reddy, K. S.; Sarkar, A.; Anand, A.; Naguib, W.; Gupta, N.; Sena, Dipaka Ranjan; Sidhu, H. S.; et al. (Elsevier, 2023)
Context: The rice-wheat cropping system in the Indo-Gangetic plains (IGP) of South Asia has been shown to have higher productivity. However, this benefit is offset by the unsustainable over-drafting of groundwater resources. Given the growing scarcity of water, it is imperative to investigate alternative crop establishment and irrigation methods that do not rely on the conventional puddled transplanting method (PTR). Objective: This study aims to assess the impact of combining conservation agriculture-CA with sub-surface drip irrigation-SSD referred to as CA+, at different nitrogen (N) doses on physiological performance, crop yield, irrigation and nitrogen use-efficiency, as well as farm profitability of rice in the north-western IGP of India. Method: A two-year field experiment was conducted to assess the effects of medium-term CA and the combination of CA with SSD (CA+) at three levels of N (0%, 75%, and 100% of the recommended dose), in comparison to PTR using recommended dose of nitrogen-RDN (120 kg N ha-1). Indicators of crop growth (under CA, CA+), i.e., biomass, grain yield, water-use, water-use efficiency (WUE), nitrogen-use efficiency (NUE), and economic analysis of rice production were evaluated and compared with PTR. Result: The results revealed that the PTR plots produced 15% and 11% higher grain yield than CA and CA+ systems, respectively, even at 100%RDN, due to a significantly higher number of fertile tillers. However, the application of 100%RDN and irrigation through SSD resulted in a significant increase in nitrogen uptake (4.5%) and remobilization (7.5%) into the grain compared to PTR. The CA+ plots demonstrated a reduction in irrigation water usage by 1.5 and 2 times compared to the CA and PTR systems, leading to a respective increase in WUE by 1.6% and 1.8%. PTR exhibited highest net returns, while the CA+ treatment– SSD-N100 achieved the highest benefit-cost ratio. Conclusion: The combination of CA with SSD at 100%RDN offers significant benefits, including notable water saving, improved WUE, NUE and crop yield. This integrated approach presents a promising solution to address the pressing issues of food security and sustainability arising from water scarcity and groundwater depletion in South Asia. Future implication: There is a need to increase awareness among farmers about the benefits of CA coupled with SSD i.e., CA+ , for water-intensive rice-based systems. Additionally, further research should focus on identifying ideal rice cultivars suitable for CA+ systems and determining the optimal specifications for drip lines and emitter discharge rates for diverse water-scarce agro-ecological conditions.